Preferencje mieszkańców Białegostoku względem leśnych usług rekreacyjnych – potrzeba aktywności fizycznej - Smoleński, Marcin (Leśne Prace Badawcze, 2016)
This paper focuses on the market segmentation of recreational forest services using the concept of ‘sensation seeking’for describing recreational expectations of town dwellers. The physical activity of town dwellers from the urban agglomeration of Białystok and the Knyszyn Forest (North-Eastern Poland) during outdoor recreation was analysed using this concept. The results of this research suggest that less than thirty percent of inhabitants of the Białystok agglomeration tend to be physically active during outdoor recreation. This is evidence of a low level of physical culture within the part of the society analysed in this study. Amongst all participants, only seven percent use the Knyszyn Forest for recreational purposes based on physical activity. The limited interest in active recreation in forests that we observed can be attributed to two main causes: 1) the lack of acceptance of a closed forest landscape as a recreational area; 2) the lack of recreational facilities in the Knyszyn Forest that would encourage healthy behaviour during active outdoor recreation.